Input-output analysis: Revenue facilites in Batam, Bintan and Karimun free trade zone - Yulifar Amin Gultom (Universitas Ahmad Dahlan, 2023)
Indonesia has four regions declared as free trade zone, which is Sabang, Batam, Bintan, and Karimun. However, Government Regulation Number 41 2021 only puts a lot of focus in the development of Batam, Bintan and Karimun. This study aims to see the impact of free trade zone as a facility given by government using input-output analysis. The impact will be measured as multiplier effect. The usage of input-output analysis differentiate this study with prior research. Input-output analysis is also used to provide priority sector of Batam, Bintan, and Karimun. This study finds that free trade zone facility provides total impact of Rp20.161,02 billion, but also shows that Batam, Bintan, and Karimun (Riau Islands Province) only provides the lowest multiplier effect compares to other provinces. By using priority sector, this study shows that from 22 development themes of Batam, Bintan, and Karimun, only 14 themes are worthy to be sustained and done. Therefore, the government needs to accelerate the integration within Batam, Bintan, and Karimun and other regions around them to boost their multiplier effect. Government also needs to reanalyze the feasibility of Batam, Bintan, and Karimun’s development themes. This study implies that from input-output analysis can be derived how effective the revenue facility given and what sectors which government needs to focus on to develop Riau Islands’ economies better. This study uses 2016 interregional input-output table, next study can be done using the latest interregional input-output table.